Cool water vs warm water immersion for minimal sedation colonoscopy: a double‐blind randomized trial. (24th October 2013) - Falt, P.; Šmajstrla, V.; Fojtík, P.; Tvrdík, J.; Urban, O.
Abstract: Aim: Water‐aided insertion as an alternative colonoscopy technique reduces patient discomfort. Warm water has been used in most published trials, but the use of cool water is easier and, if equally effective, could support the use of the water‐aided technique in routine practice. Method: A double‐blind, randomized, single‐centre study was performed in which 201 patients were randomized to either cool (20–24°C) or warm (37°C) water immersion insertion. The primary outcome was caecal intubation time. The success rate of minimal sedation and patient discomfort were also assessed. Results: The caecal intubation time for cool and warm water was similar (6.9 ± 3.5 vs 7.0 ± 3.4 min, P = 0.64). The respective success rates of minimal sedation colonoscopy (89.1% vs 90%, P = 1.00) and discomfort ( P = 0.51) were no different. All other outcomes except a greater need for abdominal compression in the cool water arm ( P = 0.04) were similar including the total procedure time, terminal ileum intubation rate, adenoma detection, length of the inserted scope, water volume, non‐standard position rate, difficulty of the procedure and the patient's temperature sensation. Conclusion: The use of cool water did not modify the caecal intubation time compared with warm water. Exception for abdominal compression, all other end‐points were no different. Cool water immersion is an alternative to the technically more demanding warm water immersion colonoscopy.